Pengaruh Brand ambassador, Promosi, dan Kualitas Produk Terhadap Minat Beli Yang Dimediasi Oleh Citra Merek (Studi Pada Konsumen Deliwafa di Kecamatan Lowokwaru) - Laila, Fati Khalif; Arifin, Rois; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the effect of brand ambassador, promotion, and product quality on consumers' purchase intention, with brand image as a mediating variable among Deliwafa Store consumers in Lowokwaru District, Malang City. A quantitative approach was employed, involving a survey of 100 female respondents aged 15–25 years using purposive sampling. Data were collected through questionnaires and analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the help of smartpls 4.0 software. The results showed that brand ambassador, promotion, and product quality positively and significantly affected both brand image and purchase intention. Moreover, brand image played a mediating role in strengthening the relationship between the independent variables and purchase intention. These findings emphasize the importance of integrated marketing strategies to enhance the competitiveness of local fashion brands. Keywords: Brand Ambassador, Promotion, Product Quality, Brand Image, Purchase Intention.